DEVELOPING A MODEL OF HOTS QUESTIONS FOR NARRATIVE READING TEXT FOR GRADE IX STUDENTS OF SMP N 2 JORONG - Simanjuntak, Evelyn; Usadiati, Wahjuningsih; Karani, Elanneri (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2019)
Teachers are required to have good reading material with various questions excercices to meet students’ interest to improve their reading ability. This developmental research was undertaken to develop a model of instructional material of HOTs questions for narrative reading texts for IX grade students of SMPN 2 Jorong. The development of the model in R & D research involved the following steps: needs assessment, reference study, material development, expert validation, tryout, revision, and final product. The subject of the research was the students of grade IX of SMPN 2 Jorong. The instruments to take the data were observation sheet, questionaire sheet, students’ test result, and test sheet. After all of the steps were done, the final product was in form of instructional material consisting of: Cover; Introduction, and Content. The content of the product consisted of Unit 1 and Unit 2, which contained narrative reading texts entitled Hansel and Grethel, Malin Kundang, and Rapunzel taken and modified from the internet. Each story was inserted with HOTS questions to ask the students to generalise, analyse, compare, distinguish, and to correlate.Based on the result of the expert validation, the model of HOTS questions for narrative reading texts for IX grade students of SMPN 2 Jorong was very effective and advisable to be implemented.